2021
DOI: 10.1371/journal.pone.0259380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth promoting microorganisms on tomato seedlings growing in different media conditions

Abstract: Plant growth-promoting microbes (PGPM) play vital roles in maintaining crop fitness and soil health in stressed environments. Research have included analysis-based cultivation of soil-microbial-plant relationships to clarify microbiota potential. The goal of the research was to (i) evaluate the symbiotic microorganism effects on tomato seedling fitness under stressed conditions simulating a fragile soil susceptible to degradation; (ii) compare the plant-microbial interactions after inoculation with microbial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…"In the morphological components of yield, the increase in height of biofertilized plants reflects the benefits of the symbiosis of L. esculentum M. with R. intraradices and A. brasilense alone or in co-inoculation" [27]. Authors such as Pokluda et al [28] mention similar results in the height of tomato seedlings var "Amalia" superior to 23% with the co-inoculation of Azospirillum brasilense and Glomus clarum in comparison to the control. Alvarado Carrillo [29] reported that plant height of L. esculentum var "El Cid" (Saladette type) increased 12% with mycorrhization.…”
Section: Discussionmentioning
confidence: 97%
“…"In the morphological components of yield, the increase in height of biofertilized plants reflects the benefits of the symbiosis of L. esculentum M. with R. intraradices and A. brasilense alone or in co-inoculation" [27]. Authors such as Pokluda et al [28] mention similar results in the height of tomato seedlings var "Amalia" superior to 23% with the co-inoculation of Azospirillum brasilense and Glomus clarum in comparison to the control. Alvarado Carrillo [29] reported that plant height of L. esculentum var "El Cid" (Saladette type) increased 12% with mycorrhization.…”
Section: Discussionmentioning
confidence: 97%
“…Confocal microscopy was conducted using the LSM 800 microscope (Carl Zeiss, Jena, Germany) at 590/617 nm excitation/emission for WGA AF 594, 650/668 nm for Con A AF 647, and 350/461 nm for Hoechst stain, using a 20 × 0.8 NA lens. The pictures were processed in Zen Blue 3.0 (Carl Zeiss, Jena, Germany) [23].…”
Section: Detection Of S Indica Colonisation In Cabbage Rootsmentioning
confidence: 99%